2019
DOI: 10.1002/kjm2.12072
|View full text |Cite
|
Sign up to set email alerts
|

Klotho/FGF23 axis mediates high phosphate‐induced vascular calcification in vascular smooth muscle cells via Wnt7b/β‐catenin pathway

Abstract: Vascular calcification (VC) plays as a critical role on cardiovascular disease (CVD) and acts as a notable risk factor in cardiovascular system. Vascular smooth muscle cells (VSMCs) calcification can be triggered by high phosphate treatment; however, the explicit mechanism remains unclear. In the present study, we isolated VSMCs from primary rat artery, applied β‐GP (β‐glycerophosphate) for inducing VSMCs calcification in vitro to explore the mechanism of phosphate‐induced calcification in VSMCs. Alizarin red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 32 publications
(60 reference statements)
0
24
0
Order By: Relevance
“…Conversely, shRNA-mediated knockdown of beta-catenin in CKD rats on a high-phosphate diet reduced vascular calcification [79]. Interestingly, klotho is an inhibitor of the Wnt/beta-catenin pathway [70], ameliorating high P i -induced VSMC calcification [81], as well as inhibiting osteogenic transition of these cells [82,83]. Taken together, P i induces EVA at least in part by the Wnt/beta-catenin pathway, and different treatment approaches potentially mitigate the adverse effects of P i on EVA, including klotho.…”
Section: The Endocrine Phosphate-fgf-23-klotho Axis and Premature Agementioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, shRNA-mediated knockdown of beta-catenin in CKD rats on a high-phosphate diet reduced vascular calcification [79]. Interestingly, klotho is an inhibitor of the Wnt/beta-catenin pathway [70], ameliorating high P i -induced VSMC calcification [81], as well as inhibiting osteogenic transition of these cells [82,83]. Taken together, P i induces EVA at least in part by the Wnt/beta-catenin pathway, and different treatment approaches potentially mitigate the adverse effects of P i on EVA, including klotho.…”
Section: The Endocrine Phosphate-fgf-23-klotho Axis and Premature Agementioning
confidence: 99%
“…Kidney-derived klotho is of particular interest as a potential treatment for inflammation and premature ageing in CKD, because klotho-deficient mice and patients with CKD have similar phenotypes, such as EVA and a pro-inflammatory status, and klotho is related to ageing in both humans and mice [70,72]. Similar to the NRF2 system, klotho is repressed in CKD, and stimulation of klotho can ameliorate oxidative stress and mitochondrial function [108], renal fibrosis [152], inflammation [72], as well as premature ageing [108], including EVA [55,[81][82][83][111][112][113].…”
Section: Klotho Pathwaymentioning
confidence: 99%
“…The signaling molecule Wnt7B is a positive regulator of the Wnt/β‐catenin pathway 17 . The gene for Wnt7B is located on human chromosome 22q13.3 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The signaling molecule Wnt7B is a positive regulator of the Wnt/ β-catenin pathway. 17 The gene for Wnt7B is located on human chromosome 22q13.3. 18 The Wnt7B protein is the only member of autocrine/paracrine signaling molecule group whose expression is restricted to the airway epithelium during embryonic lung development and with markedly upregulated transcription during the pseudoglandular period.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies indicate a correlation between higher FGF23 levels and increased aortic calci cation. [13,14] However, other studies have shown that FGF23 had no impact on VC [15,16] or inhibited the progression of VC [17,18]. FGF21 is also increased progressively with a decline of renal function.…”
Section: Introductionmentioning
confidence: 99%